(untitled) (The Macau Ricci Institute Journal, 2020)
François Ravary (1823-91) was a French Jesuit, an alumnus of Issenheim, Brugelette, and Laval, who went to China in 1856 to join the Jiangnan mission. He remained there for the rest of his life and is remembered for one achievement: the construction of “The Bamboo Organ of Tungkadoo”, completed in 1857. His mission, however, extended in other directions, most of them connected with music, the fine arts, and education in the context of various intercultural modes of exchange. Some of his letters have survived, detailing the rich musical culture he helped to create in mid-nineteenth century Shanghai. One of these narrates the chilling account of the murder of the Jesuit Luigi Massa by the Taiping in 1860. A corrective to a few details surrounding this tragedy, it also highlights the continuing importance of source study, epistolary research, individual (as opposed to collective) evaluation, and translation.